Pengaruh Work Life Balance terhadap Employee Performance melalui Psychological Well Being - Wati, Dita Ayu Indra; Budiono (Jurnal Ilmu Manajemen, 2024)
This research, with practical implications that can empower and motivate organizations, aims to determine and explain the influence of work-life balance on employee performance through psychological well-being. Using quantitative methods, the study employed a non-probability sampling technique with a purposive sampling type, resulting in a sample of 41 respondents. The statistical analysis used was the Structural Equation Model - Partial Least Square (SEM-PLS) with SmartPLS 3.2.9 software. The results of this study reveal that work-life balance has a positive and significant effect on employee performance. Furthermore, work-life balance has a positive and significant effect on psychological well-being, which in turn has a positive and significant effect on employee performance. In the analysis of indirect effect, psychological well-being is found to mediate the influence of work-life balance on employee performance. This research underscores the practical implications of ensuring work-life balance, as it can reduce stress, maintain psychological well-being, and improve employee performance, thereby empowering and motivating organizations to prioritize work-life balance.